Mentoring dyads in higher education: It feels lucky, but it's more than luck. Issue 3 (17th June 2021) - Fitzgerald, Angela; McNamara, Noeleen
Abstract : Purpose: The purpose of this paper is to explore the formation, maintenance and sustenance of a mentoring dyad in higher education. By investigating the reflections of a female mentor and mentee, who both engaged in a formal Mentoring Program, the intention is to inform the design of future programs and expectations of participants, enhance the quality of future practice and understand the benefits mentoring might offer to the academic community. Design/methodology/approach: The researchers utilised a self-study research design to explore their reflections of a mentoring dyad in higher education. The project was informed by a personal–constructivist–collaborative approach, with participants maintaining journals throughout the partnership. These reflections were then compared in order to understand the perceptions of the participants as their relationship developed. Findings: Six themes emerged from the analysis representing the mentoring dyad experience under three categories: (1) forming – making the match, (2) maintaining – flexibility, responsiveness, and persistence, and (3) sustaining – desire to not disappoint and reciprocal learning. Research limitations/implications: While this paper focuses on the experiences of two participants, the in-depth nature of this exploration draws out significant practical considerations that can be applied to the development and/or reinvigoration of formal mentoring programs and/mentoring dyads in other contexts. Originality/value: These unique insights into their mentoring dyad over a significant period of time add to this dynamic body of knowledge. This study gives voice to female academics and lays bare their vulnerability and openness in sharing their lived experiences of participating in a formal mentoring program.